Real-world diagnostic value of integrating oral and ocular dryness testing in suspected Sjögren’s disease - Seyal, Eman; Akaa, Jesse; O’Dea, David; Nguyen, Thao; Rahmati, Rahmatullah W.; Law, Brandon M. (Frontiers in Medicine, 2025)
BackgroundSjögren’s disease is an autoimmune condition requiring a systemic evaluation that integrates serologic, histopathologic, and glandular assessments for diagnosis. Current 2016 ACR/EULAR classification criteria includes anti-Ro serology, labial salivary gland biopsy (LSGB), and measures of oral/ocular dryness. However, oral/ocular dryness evaluations are rarely performed by rheumatologists during routine clinical care. Thus, the real-world diagnostic value of contemporaneous oral/ocular dryness testing remains poorly understood.ObjectiveTo evaluate the added value of contemporaneous oral/ocular dryness testing (Schirmer’s test and unstimulated whole salivary flow) in meeting classification criteria for subjects evaluated with suspected Sjögren’s disease.Methods73 subjects referred for suspected Sjögren’s disease were evaluated. Correlations between LSGB results and dryness tests, as well as LSGB results and anti-Ro serology, were evaluated. 31 subjects completed testing of oral/ocular dryness (Schirmer’s test and unstimulated whole salivary flow), anti-Ro serology, and LSGB. Diagnostic pathways were analyzed to assess the contributions of non-invasive tests (serologies and oral/ocular dryness tests) and invasive testing (LSGB) in meeting the threshold for classification criteria.ResultsA significant association (p-value = 0.0263) was observed between LSGB positivity and positive Schirmer’s testing. No significant association was observed between LSGB positivity and anti-Ro positivity, or between LSGB positivity and low unstimulated whole salivary flow. Among those meeting classification criteria for Sjögren’s disease, 81% (30/37) met classification independently of LSGB results. Of those who completed testing, 22 met classification, among whom 68% (15/22) fulfilled criteria independently of LSGB results. Of these 15 subjects, 8 (53%) had negative LSGB with a focus score <1. While a positive LSGB was mandatory to confirm classification for seronegative subjects, only 11.8% (2/17) of anti-Ro-positive subjects required LSGB for classification.ConclusionObjective oral/ocular dryness testing, though rarely performed in routine rheumatologic care, is a valuable complement to serology and biopsy in diagnosing Sjögren’s disease. While LSGB is essential for confirming classification in anti-Ro-negative subjects, it adds only modest value to meeting classification criteria in anti-Ro-positive subjects relative to contemporaneous glandular dryness testing. These findings support integrating objective dryness measures into routine diagnostic workflows to reduce reliance on invasive biopsies and improve diagnostic accuracy, especially in seropositive populations.